(untitled) (Journal of Medical Sciences, 2022)
Although Candida is a kind of a normal flora of the mucous membranes in the respiratory, gastrointestinal and female genital tracts, its scope of infections is increasing all over the world as a result of their resistance. It is known that certain honey types have significant antifungal activity against range of Candida species; therefore this study has focused on the evaluation of the antimicrobial activity of the Libyan spring honey against Candida species. Concentrations of 50 % and 25 % of Libyan spring honey were prepared and tested for antimicrobial activity against Candida albicans samples that were collected as random samples of human mouth. It was concluded that 25 % and 50 % concentration of Libyan spring honey has no effect on the growth of C. albicans. On the other hand it was clearly observed that the Libyan spring honey was very affective in inhibiting the candial adherence to buccal epithelial cells (BEC) in vitro.